An experimental study on mechanical and durable properties of self-curing concrete by adding admixture. (2020) - Vijayan, D.S.; Arvindan, S.; Parthiban, D.; Kumar, R. Sanjay; Saravanan, B.; Robert, Yumnam
Abstract: In this investigation the river sand was replaced with Manufactured Sand (M- Sand) by 50% and 100% mix. Self- curing of concrete is enhanced by polyethylene glycol which increases hydration and strength properties of concrete. It also shows the effect of Polyethylene glycol on compressive strength, split tensile strength by 0.3% percentage of PEG(1500) by weight of cement were studied for 50% and 100% replacement of manufactured Sand with different grades of concrete. For the specimen with 1% of self –curing agent, the mix showed highest compressive strength when compared to other mixes with self-curing agent (i.e. 1.5% and 2%). The mix with 1% of PEG showed compressive strength marginally greater than the compressive strength of conventional concrete.